EDUCATIONAL PARADIGM TRANSFORMATION IN THE CONTEXT OF GREEN ECONOMY - A. A. Muravyeva; O. N. Oleynikova (Obrazovanie i Nauka, 2016)
The aim of the article is to present vectors of Vocational Education Training (VET) modernization in the context of the sustainable development and green economy development; as well as to offer a perspective on addressing the existing gaps based on international experience.Methods. The methods involve the comparative-analytical method, method of conceptual and socio-cultural contextualization, method of rationalization of meaning, foresight methods and methods of social projection. Results of the research confirm the thesis that education as a social subsystem reflects the main trends of social development, as far as it is not only an instrument for ensuring of cultural and historical succession, but also the system of forming of a personality and behavior of citizens understanding degree of the responsibility for own future and having for this purpose necessary professional and universal (common cultural) competences and valuable attitudes. It is convincingly proved that for sustainable development of the society and economy, the operational solution of a complex triune task is required: upgrading of educational programs, improvement of competences of teachers and creation of the new training environment. Besides the goal setting and identification of the existing gaps and contradictions that block its decision, the specific measures approved at the international level are proposed; these measures should be integrated into the Russian social and educational context. Professional education at the same time is considered both as an object, and as the instrument of necessary changes. Scientific novelty lies in the contextualization of the challenges of sustainable development and their extrapolation onto the system of vocational education in the form of system-level projecting approaches.Practical significance. The materials of the publication are offered to be used for development of the strategy of improvement of vocational education; for planning and implementation of practical organizational and substantial actions for «green» transformation of educational institutions. The results of the provided research will be also useful in case of creation of programs for system of continuing vocational education of teachers, methodologists and heads of educational organizations.